Overview of Rural Youth in Malaysia - Md Nor, Noranifitri; Md Ramlan, Saiful Farisin; Johar, Siti Sarawati (Human Sustainability Procedia, 2025)
Youth is an important asset in the development of a country, The existence of youth groups plays a major role in various sectors in the country covering the economic, political, and social sectors. In Malaysia, youth include those aged 15 to 30 years, with a variety of backgrounds, aspirations, and challenges they face. This article discusses the situation of Malaysian youth from the perspective of socio-economic, educational opportunities and challenges, healthcare and mental health, economic opportunities and challenges and social support and community involvement. By understanding the dynamics of youth, more inclusive and effective policies can be formulated to support their development as future leaders of the country.